Pendampingan Digitalisasi Produk UMKM PKK di Desa Sumberejo Wonogiri Melalui Branding dan Digital Marketing - If Bambang Sulistyono; Eusthacia Arzeti Kushandi; Maharani Putri Intan Nurhaliza; Sekar Arum Kusuma Jati; Sekar Poetry Mahardhika (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
This community service activity aims to increase the knowledge and skills of the Sumberejo Wonogiri Village PKK and MSMEs owners in utilizing social media as a means of developing business. This activity is carried out through socialization and training methods which aim to provide understanding and awareness for Sumberejo Village MSMEs players in utilizing digital media as a means of marketing products. The participation and enthusiasm of the Sumberejo Village PKK and MSMEs owners in the activity was very good. The impact of the socialization activities was able to increase the knowledge and skills of the Sumberejo Village PKK and MSMEs owners in increasing market expansion through digital marketing. The Socialization of MSMEs Branding in the Context of Market Expansion in Sumberejo Village is very useful and is expected to be sustainable.